2017
DOI: 10.1038/srep43097
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid B inhibits mitochondrial dysfunction by up-regulating mortalin

Abstract: Salvianolic acid B is an antioxidative ingredient derived from Radix Salviae miltiorrhizae that has been widely used to treat liver diseases. However, the therapeutic mechanism underlying Salvianolic acid B has remained largely unknown. Our studies verified that Salvianolic acid B efficiently blocked mitochondrial deformation and dysfunction induced by H2O2 in the human hepatocyte cell line HL7702. Mortalin, a mitochondrial molecular chaperone, maintains mitochondrial morphology stabilization and function inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…Sal B is a major water-soluble polyphenolic antioxidant in Radix Salviae Miltiorrhizae and has been extensively used in clinics in China[ 23 - 25 ]. Sal B possesses efficient radical scavengers and antioxidants[ 14 , 26 , 27 ]. Previous reports have shown that Sal B exerts therapeutic effects in treating liver fibrosis[ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sal B is a major water-soluble polyphenolic antioxidant in Radix Salviae Miltiorrhizae and has been extensively used in clinics in China[ 23 - 25 ]. Sal B possesses efficient radical scavengers and antioxidants[ 14 , 26 , 27 ]. Previous reports have shown that Sal B exerts therapeutic effects in treating liver fibrosis[ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown to moderate lipid metabolism in high-fat diet-induced obese mice by suppressing peroxisome proliferator activated receptor gamma (PPARγ)- mediated adipogenesis ( Wang et al, 2014 ). SalB has also been found to improve the integrity of mitochondria and block mitochondria deformation and dysfunction induced by H 2 O 2 ( Xu et al, 2011 ; Liu et al, 2017 ). However, the effects of SalB on mitochondrial function in 3T3-L1 cells remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Sal B inhibited the proliferation of LX-2 cells and down-regulated the expression of α-SMA protein (Hou et al, 2011). The study also found that Sal B protected the liver from damage by effectively blocking H 2 O 2 -induced mitochondrial deformation and dysfunction in the human liver cell line HL7702 (Liu et al, 2017).…”
Section: Effects Of Salvianolic Acids On Fibrosis Diseasementioning
confidence: 78%